2014
DOI: 10.9790/2380-0712298102
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on Dynamics Soil Properties and Forms of Sulphur in Oilseed Growing Soils of Ambajogai Tahsil of Beed District

Abstract: The present

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…All the forms of S (total S, organic S, inorganic S and available S) and SOC showed significant negative correlation with pH of the soil. Soil organic carbon maintained significant positive correlation with all forms of S. Das et al (2011) and Dhamak et al (2014) also reported significant positive correlation of SOC with different forms of S. The negative relationship between pH and forms of S may be due to the presence of H + and OHin the soil complex which binds the SO 4 2ions rendering it unavailable (Borkotoki and Das, 2008). Total S maintained significant positive correlation with all forms of S indicating a state of dynamic equilibrium in the soil.…”
Section: Effect Of Land-use Pattern On Distribution Of Different Forms Of Sulphur Along the Soil Depthmentioning
confidence: 90%
See 1 more Smart Citation
“…All the forms of S (total S, organic S, inorganic S and available S) and SOC showed significant negative correlation with pH of the soil. Soil organic carbon maintained significant positive correlation with all forms of S. Das et al (2011) and Dhamak et al (2014) also reported significant positive correlation of SOC with different forms of S. The negative relationship between pH and forms of S may be due to the presence of H + and OHin the soil complex which binds the SO 4 2ions rendering it unavailable (Borkotoki and Das, 2008). Total S maintained significant positive correlation with all forms of S indicating a state of dynamic equilibrium in the soil.…”
Section: Effect Of Land-use Pattern On Distribution Of Different Forms Of Sulphur Along the Soil Depthmentioning
confidence: 90%
“…Similar positive relationship among various forms of sulphur was earlier reported by Tripathi et al, (2000); Das et al, (2012) and Javed et al, (2014). Correlation studies (Table 2) indicated that organic S maintained a high significant correlation with SOC content indicating that SOC is the main source of organic S. Reports were there also regarding the strong association of organic S and SOC content of soils (Borkotoki and Das, 2008;Javed et al, 2014 andDhamak et al, 2014).…”
Section: Effect Of Land-use Pattern On Distribution Of Different Forms Of Sulphur Along the Soil Depthmentioning
confidence: 95%
“…The NI value for potassium status was found to be 2.49 and is depicted in figure 2. Variation in available potassium across the soils of different districts was noticed by several workers (Rezo et al, 2007;Sharma et al, 2009;Pulakeshi et al, 2012;Dhamak et al, 2014) and was attributed to variation in mineralogical compositions.…”
Section: Available Potassium (Kg Ha -1 )mentioning
confidence: 96%
“…Calcium carbonate in soil varied from 63.00 to 69.00 g kg -1 at 0-15 cm depth and 64.00 to 70.00 g kg -1 at 15-30 cm depth but it was not much influenced by different nutrient management practices and increased with depth of soil. Increase in subsurface layer due to leaching of Ca and subsequent participation as a carbonate at a lower depth (Dhamak et al 2014 andWaikar et al 2003) [3,15] .…”
Section: Changes In Soil Physic-chemical Propertiesmentioning
confidence: 99%